EFEKTIVITAS UNITED NATIONS MISSIONS ORGANIZATION IN THE DEMORCATIC REPUBLIC OF THE CONGO (MONUC) DALAM KONFLIK DI REPUBLIK DEMOKRASI KONGO - Abdul Latif; Ahmad Jamaan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2014)
This research describes effectiveness of MONUC while maintained their missions as peacekeeper in Democratic Republic of the Congo. It examines the missions that MONUC did during 1999 until 2010. MONUC is a peacekeeping mission authorized by United Nations Security Council. Its initial aims were to watch the implementation of Lusaka Ceasefire Agreement, ceasefire agreement of Congo War II. Later, its aims were expanded due to the complexity of conflicts in Democratic Republic of the Congo until June 2010. Its capability also changed from the traditional peacekeeper based on Chapter VI UN Charter became more robust mission, adopted from Chapter VII UN Charter. However, the presence of MONUC in Democratic Republic Congo was unable to prevent to massive victims of the sporadic conflicts. Mass murder, rape, looting, and other human right abusive acts, occurred in the country left MONUC had nothing much to do. This research is a qualitative research. It uses the library research method with that collecting secondary data from books, journals, and internet. It uses international organization theory and organization effectiveness to explain MONUC during working its mandates. The result of this research shows MONUC was ineffective on its missions. It failed to protect the civilians as protection is its ultimate goal in the country.Keyword: Democratic Republic of the Congo, effectiveness, MONUC, peacekeeping, rebellion